Different classes of antibiotics have varying effects on the risk of developing opioid use disorder: a national database study. - Clegg, Taylor J.; Kawmi, Noor; Graziane, Nicholas M. (Journal of Substance Use, 2023)
To examine whether different classes of antibiotics in combination with opioids differentially effect the risk of developing opioid use disorder (OUD). A cohort study was conducted to identify adult subjects (18–65 years old) with no previous history of OUD. Two cohorts were defined: subjects who were prescribed an opioid or an opioid in combination with antibiotics in the emergency department or inpatient unit, from the years 2015 to 2018. The diagnosis of an Opioid Related Disorder (F11.10-F11.20) 12 months following discharge from the emergency department or inpatient unit was then observed within the cohorts following the index event as identified by the ICD-10 procedural coding system. Primary analysis showed that penicillin G had no statistically significant effect, while the following list of antibiotics were associated with increased risk of developing OUD in order from highest to lowest risk: cefepime > tazobactam > ertapenem > doxycycline > ceftriaxone, sulfamethoxazole > clindamycin > azithromycin > ciprofloxacin > penicillins > cefazolin > amoxicillin > penicillin V. These findings suggest that the type of antibiotic prescribed in combination with opioid treatment may have important implications on the risk of developing OUD at later time points following hospital discharge.